INTEGRATIVE OF DRAWING GEOMETRY APPROACHES - Tangirov Behzod Karshiyevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article provides information about the goal tasks of drawing geometry, the branch of geometry that studies the methods of depicting spatial figures on a plane and solving spatial problems using them.